Analisis Inovasi Berbasis Teknologi Dalam Keunggulan Bersaing Pada Pengalaman Pelanggan Serta Loyalitas Pelanggan Di Industri Perhotelan Kabupaten Jember - Sandy, Syah Riza Octavy; Faozen, Faozen (RELASI : JURNAL EKONOMI, 2024)
This research aims to examine technology-based innovation in competition excellence, customer experience, customer loyalty in the hotel industry in Jember Area. So that through this research we can provide reference ideas for stakeholder partners, namely Hotel Indonesia Jember Branch and Restaurant Association (PHRI) and more specifically hotel services business actors as a reference in making policies in responding to hotel marketing strategies that correlate with customer practices and customer loyalty. This The research aims to find out and test technology-based innovation competitively excellence, customer experience, customer loyalty in the hotel industry (Case III Star Hotel Study in Jember Regency). The population of this study is Hotel guests. This activity stage begins with a survey, namely testing research instrument. After obtaining a valid instrument, the research team then left go to the field to dig up information by interviewing and distributing questionnaires to obtain primary and secondary data. The data obtained are processed using a statistical processing application program. The next stage is prepare a final report based on the results of data and scientific analysis publication as the output of this research.